An exploratory study on isochoric supercooling preservation of the pig liver - Botea, F., Năstase, G., Herlea, V., Chang, T. T., Șerban, A., Barcu, A., Rubinsky, B., & Popescu, I. (Elsevier B.V., 2023)
This study was motivated by the increasing interest in finding ways to preserve organs in a supercooled state for transplantation. Previous research with small volumes suggests that the isochoric (constant volume) thermodynamic state enhances the stability of supercooled solutions. The primary objective of this study was to investigate the feasibility of storing a large organ, such as the pig liver, in a metastable isochoric supercooled state for clinically relevant durations. To achieve this, we designed a new isochoric technology that employs a system consisting of two domains separated by an interior boundary that can transfer heat and pressure, but not mass. The liver is preserved in one of these domains in a solution with an intracellular composition, which is in osmotic equilibrium with the liver. Pressure is used to monitor the thermodynamic state of the isochoric chamber. In this feasibility study, two pig livers were preserved in the device in an isochoric supercooled state at -2◦C. The experiments were terminated voluntarily, one after 24 h and the other after 48 h of supercooling preservation. Pressure measurements indicated that the livers did not freeze during the isochoric supercooling preservation. This is the first proof that organs as large as the pig liver can remain supercooled for extended periods of time in an isotonic solution in an isochoric system, despite an increased probability of ice nucleation with larger volumes. To serve as controls and to test the ability of pressure monitoring to detect freezing in the isochoric chamber, an experiment was designed in which two pig livers were frozen at -2◦C for 24 h and the pressure monitored. Histological examination with H&E stains revealed that the supercooled liver maintained a normal appearance, even after 48 h of supercooling, while tissues in livers frozen to -2◦C were severely disrupted by freezing after 24 h.